2021
DOI: 10.1017/pen.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

Early and late signals of unexpected reward contribute to low extraversion and high disinhibition, respectively

Abstract: Like socio-economic status and cognitive abilities, personality traits predict important life outcomes. Traits that reflect unusually low or high approach motivations, such as low extraversion and high disinhibition, are linked to various forms of mental disorder. Similarly, the dopamine system is theoretically linked to approach motivation traits and to various forms of mental disorder. Identifying neural contributions to extremes of such traits should map to neural sources of psychopathology, with dopamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…The samples used for the present study have been used in other studies to address other research questions (Kremyar & Wygant, 2023;Lagera & Sellbom, 2023;Neo et al, 2021;Sellbom, 2021;Sellbom et al, 2021Sellbom et al, , 2022Whitman & Sellbom, 2023). The research questions and results presented in this study are novel and have not been presented in these previous peer-reviewed publications.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…The samples used for the present study have been used in other studies to address other research questions (Kremyar & Wygant, 2023;Lagera & Sellbom, 2023;Neo et al, 2021;Sellbom, 2021;Sellbom et al, 2021Sellbom et al, , 2022Whitman & Sellbom, 2023). The research questions and results presented in this study are novel and have not been presented in these previous peer-reviewed publications.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…While they completed the questionnaires, the experimenter prepared the participants for EEG recording by applying electro-gel and reducing the impedance of the recording sensors attached to the EEG cap. The participants were then tested (∼25 min) on the stop-signal task (Shadli et al, 2015 ), followed by the gold bar/lemon task (Neo et al, 2021 ) (∼30 min; data not reported here). The participants were then administered the structured clinical interviews.…”
Section: Methodsmentioning
confidence: 99%
“…They subsequently completed the study measures via the Qualtrics platform. Next, they completed a full electroencephalogram (EEG) protocol for approximately 1 hour (which was not used for this study; see Neo et al, 2021). After completing the EEG measures, the SCID-5 and SCID-5-PD modules were administered to each participant.…”
Section: Methodsmentioning
confidence: 99%